Ethical Issues in Intensive Care Units during the COVID-19 Pandemic - Karampelias, Vasileios (Indian J Crit Care Med, 2020)
Coronavirus disease-2019 (COVID-19) outbreak began in December 2019 in China and has spread rapidly across the world. The healthcare system of each country has been affected from this situation. Undoubtedly, during this period several ethical issues have been raised. In this commentary, we aimed to make a discussion regarding the ethical issues that could be raised in the treatment of patients in the intensive care units during the COVID-19 pandemic. The objective of this article is to contribute to the wide current discussion regarding the appropriate measures that should be taken to protect the health and ensure the safety of the staff that comes in close contact with patients who are suspected or confirmed of having COVID-19. How to cite this article: Karampelias V, Spanidis Y, Roussakou E. Ethical Issues in Intensive Care Units during the COVID-19 Pandemic. Indian J Crit Care Med 2020;24(9):855–856.